A Pilot Study on the Opportunities and Challenges among SME Tourism in the Heritage Food Industry in Kota Kinabalu, Sabah - Putriku Nuraishah Khairanni Asby; Adilah Md Ramli; Kamarul Mizal Marzuki; Teuku Afrizal Teuku Anuar (Association of Malaysian Environment-Behaviour Researchers, 2024)
Study based on small and medium entrepreneurs (SME) shows that tourism has increased since 2019. However, the involvement of Tourism SMEs in the food heritage industry still needs to be improved. A qualitative research design was proposed to investigate the matter, and a pilot study was initiated. This paper aims to understand opportunities in the heritage food industry and explore the challenges. Tourism SMEs of food heritage producers are the informants to understand their business. This pilot study was done to help researchers gain first-hand experience with the settings and data collection to strengthen their confidence in executing the research.